O perspectivă asupra ocupării atipice: România în comparaţie europeană - Ilie, Simona; Preoteasa, Ana Maria (Calitatea Vieții, 2017)
The article carried out an analysis of employment situation in Romania. The study refers to the different aspects that could conduct to labor market vulnerability. There are considered the main drivers towards precarious work: low revenues, types of employment contracts, contract durations or working conditions. The analysis uses both statistical data (INSSE, Eurostat) and surveys data (Eurfound), looking either longitudinally or in international comparison with European countries. The concluding part of the paper, provides an analysis of the Romanian employment policies, essential in encompassing the employment precariousness and offers a collection of recommendations able to address the issue of precarious work.